ECONOMETRIC STUDIES FOR FORECASTING INCREASE IN YIELD OF AGRICULTURAL CROPS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses forecasting based on econometric research, being the basis of scientifically based planning decisions, increasing the scientific level of planning and as one of the foundations of the scientific knowledge base methodologies should serve as a tool to support the concept of medium and long-term planning, systematic analysis and optimal decision-making.